DEPRESSION AMONG PARENTS OF CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Iqbal, Akhtar; Siddiqui, Khawer S. (Journal of Ayub Medical College Abbottabad, 2002)
Background: The diagnosis of cancer in children can always be devastating to the patients as well as to their parents. Some degree of depression is to be expected among parents caring for a loved one with leukemia. This study was done to determine the frequency of depression in parents of children with acute lymphoblastic leukemia in relation to age, gender, education, occupation, and performance status of their patients. Methods: The study was conducted at Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan over a period of three months, from May, 2000 to July, 2000. Either parent of 60 consecutive patients of acute lymphoblastic leukemia who achieved their first remission within last one-month were enrolled. Their age, gender, education, occupation, socioeconomic status, and non-medical risk factors of depression were recorded. The Mini Mental State Examination (MMSE) and Structured Clinical Interview according to the Diagnostic and Statistical Manual of Mental Disorders - fourth version (SCID - IV) were used to identify parents with depression. Data regarding sociodemographic variables and non-medical risk factors of depression were recorded on data capture form. Data analysis was done by SPSS - 10. Overall differences were assessed using percentages and chi-square. Results: Depression was found to be positive among 56.7% (34) of the parents. It was more common among mothers, less educated parents and among those belonging to lower socioeconomic class. Parents attributed their depression to multiple factors; most common were related to concerns about family’s well-being, financial constraints and distressing change in role and responsibilities. Conclusion: This study concludes that a majority of attending parents of children with acute lymphoblastic leukemia suffers from depression and it is not associated with any of the variables studied. We need to conduct further studies on a large number of parents in order to make any logical conclusions. Key Words: Depression, Parents, Children, Leukemia, Cancer.